2005
DOI: 10.1021/jf0500785
|View full text |Cite
|
Sign up to set email alerts
|

One- and Two-Dimensional Electrophoretic Identification of IgE-Binding Polypeptides ofLupinus albusand Other Legume Seeds

Abstract: The prevalence of food allergies in the world population requires integrated approaches to identify new potential allergens, especially those of plant origin. The aim of this work was the allergen in vitro analysis of Lupinus albus seed proteome, a promising food protein source, and the assessment of IgE cross-reactivities with other more diffused legume species. A combination of one- and two-dimensional gel electrophoresis and immunoblotting analyses with specific IgGs for band identification and lupin-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
50
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 23 publications
19
50
3
Order By: Relevance
“…The observed cross-reactivity may be due to the fact that the lupin β-conglutin fraction, within which the mentioned proteins are present and exhibits high sequence homology with the main peanut allergen Ara h 1 [31]. Magni et al [16] based on results obtained from 2-DE and immunoblotting stated that lupin proteins reacting with IgE antibodies of lupin sensitive individuals belong to fractions of α-and γ-conglutin. On the other hand, Goggin et al [17] utilising the same methods showed that major allergen of L. angustifolius are proteins from β-conglutin fraction.…”
Section: Antigenic Properties Of Lupin Seed Proteins and Their Hydrolmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed cross-reactivity may be due to the fact that the lupin β-conglutin fraction, within which the mentioned proteins are present and exhibits high sequence homology with the main peanut allergen Ara h 1 [31]. Magni et al [16] based on results obtained from 2-DE and immunoblotting stated that lupin proteins reacting with IgE antibodies of lupin sensitive individuals belong to fractions of α-and γ-conglutin. On the other hand, Goggin et al [17] utilising the same methods showed that major allergen of L. angustifolius are proteins from β-conglutin fraction.…”
Section: Antigenic Properties Of Lupin Seed Proteins and Their Hydrolmentioning
confidence: 99%
“…In the case of lupin the most frequent reactions occurred in peanut sensitive individuals [5,6,14]. Fractions of α-and β-conglutin are considered to be the main proteins that cause allergic reactions in patients with known allergies to peanuts [15][16][17]. Recent studies in this subject were carried out by Ballabio et al [18].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to bind specific antibodies is especially important for the allergenicity of lupin seeds. The main IgE-binding proteins of lupin have molecular weights in the range from 70 to 60 kDa and 40 kDa (β-conglutin) [21], 30 and 17 kDa (γ-conglutin) [20] and 20 kDa (basic subunit of α-conglutin) [20]. Serious health risk associated with food allergy is the presence of cross-reactions, which in the case of lupin most often occurs with other legumes [18,19].…”
Section: Immunoreactive Properties Of Digested Lupin Seed Globulinsmentioning
confidence: 99%
“…In the case of lupin, the most frequently observed cross-reaction is the one with peanut [9,10,18]. The main proteins that cause allergic reactions in patients with known allergies to peanuts are these included in the α-and β-conglutin fractions [19][20][21]. Ballabio et al [22] analysing the allergic reaction in twelve patients with allergy to peanuts found that seven of them reacted positively to β-conglutin.…”
Section: Introductionmentioning
confidence: 99%
“…Other cereal flour adulterants include, but are not limited to, mungbean powder in spirulina, cornstarch in lotus root powder, and lupin bean in wheat flour (Pompei et al, 1985;Parisot et al, 2001;Magni et al, 2005;Scarafoni et al, 2009).…”
Section: Othersmentioning
confidence: 99%